Investigation of Spatial Organization of Chromosome Territories in Chromosome Exchange Aberrations After Ionizing Radiation Exposure. Issue 1 (July 2018) - Balajee, Adayabalam S.; Sanders, Jacob T.; Golloshi, Rosela; Shuryak, Igor; McCord, Rachel Patton; Dainiak, Nicholas
Abstract : Abstract: Higher-order organization of the human genome is well established with chromosomes occupying distinct domains or territories in the interphase nucleus. Spatial organization of chromosome territories in the interphase nucleus occurs in a cell-type-specific manner. Since both stable and unstable aberrations induced by ionizing radiation involve the exchange of material between two or more chromosomes, this study investigated the role of spatial organization of chromosome domains in ionizing-radiation-induced chromosome translocation events. Using multicolor fluorescence in situ hybridization, the study characterized the positioning of each human chromosome relative to its neighborhood territories in the interphase nucleus of lymphocytes and B-lymphoblastoid cells before ionizing radiation and compared this interphase positioning with the spectrum of exchanges observed after ionizing radiation in the metaphase chromosomes. In addition to multicolor fluorescence in situ hybridization, the genome-wide chromosome conformation capture technique (Hi-C) was also performed in mock and x-ray-irradiated human B-lymphoblastoid and fibroblast cells to characterize the interactions among chromosomes and to assess the genome reorganization changes, if any, after ionizing radiation exposure. On average, 35–50% of the total translocations induced by x rays and neutrons correlated with proximity of chromosome territories detected by multicolor fluorescence in situ hybridization in both lymphocytes and lymphoblastoid cells. The translocation rate observed in proximally positioned chromosome territories was consistently higher than distally located territories and was found to be statistically significant ( p = 0.01) in human lymphoblastoid cells after x rays. The interchromosome interaction frequencies detected by Hi-C correlate fairly well with ionizing-radiation-induced translocations detected by multicolor fluorescence in situ hybridization, suggesting the importance of chromosome proximity effects in ionizing-radiation-induced chromosomal translocation events.